The Importance of Infrastructure Management for Improving the Quality and Quality of Elementary School Learning - Hanisah Nur Dinei (Edumaspul: Jurnal Pendidikan, 2023)
This studyi examinesi thei importancei ofi thei managementi ofi facilitiesi andi infrastructurei ini improvingi thei qualityi ofi education.i Thei purposei ofi thisi researchi isi toi findi outi howi thei managementi ofi thei procurementi ofi infrastructurei andi howi importanti infrastructurei isi ini improvingi thei qualityi ofi education,i especiallyi ini elementaryi schools.i Thisi researchi wasi conductedi usingi ai qualitativei approachi andi datai collectioni techniquesi fori thisi studyi usingi literaturei studies.i Thei resultsi ofi thei studyi showi thati thei managementi ofi infrastructurei isi veryi importanti ini improvingi thei qualityi ofi education.i Thisi cani bei seeni fromi 1)i thei notioni ofi infrastructure,i namelyi onei ofi thei supportingi factorsi fori thei implementationi ofi ani effectivei andi efficienti learningi process;i 2)i Thei understandingi ofi infrastructurei management,i namelyi thei processi ofi procuringi andi utilizingi componentsi directlyi ori indirectlyi toi achievei educationali goalsi effectivelyi andi efficiently:i 3)i infrastructurei managementi process,i namelyi thei processi ofi planning,i procurement,i use,i inventory,i maintenance,i andi elimination;i andi 5)i infrastructurei andi educationi qualityi improvement,i namelyi schoolsi thati havei adequatei facilitiesi andi infrastructurei willi bei ablei toi improvei thei qualityi ofi educationi ini ani institution.